Strategy of Surgical Treatment of Patients with Pigment Dispersion Syndrome and Myopia - S. N. Sakhnov; O. A. Klokova; P. A. Karagodina; T. I. Arlanova; A. A. Leonova (Oftalʹmologiâ)
Purpose: to conduct a prospective study of the results of surgical treatment of patients with pigment dispersion syndrome and complex myopic astigmatism. Materials and methods. As a result of a comprehensive examination of 10453 adult primary patients with complex myopic astigmatism, the diagnosis of pigment dispersion syndrome was made in 99 patients (0.94 %). The study group consisted of 22 people, 9 men and 13 women, with an average age of 29.4 ± 9.8. In the case of iridosonular contact, according to ultrasound biomicroscopy, laser basal iridectomy was performed at the first stage. In the case of normal intraocular pressure indicators, laser correction of myopia was made in patients of the study group within 6 months after laser basal iridectomy. Results. During biomicroscopy, a Krukenberg spindle was observed in 34 eyes (77.2 %), exogenous pigment was detected in 20 eyes (45.4 %) on the iris and lens, and sectoral illumination of the iris was detected in 5 (11.4 %). After laser basal iridectomy on 24 eyes (54.5 %) in all the studied meridians, we noted a tendency to deepen the posterior chamber, but the increase was statistically significant only at 12 hours (P < 0.05). The achieved decrease in the angle of the anterior chamber was statistically significant (P < 0.05) in the meridians of 3, 9 and 12 hours and ranged from 3.56 to 8.53 degrees in different meridians. Laser correction of complex myopic astigmatism was performed in 11 patients (22 eyes) using ReLEx® SMILE technology and 10 (20 eyes) patients using FemtoLASIK technology. At the end of the observation period after correction, refraction within ±0.5 dptr of the planned one was achieved in 88.1 % of cases (37 eyes), ±1.0 dptr — in 100 % of cases. The efficiency coefficient was 88.46 %, the safety coefficient was 92.8 %. Postoperative values of corneal-compensated IOP were comparable with preoperative indicators (P > 0.05). Conclusions. The analysis of the of surgical treatment results in the patients with pigment dispersion syndrome and myopia showed the absence of negative dynamics in the course, as well as high efficiency, safety and stability of the results achieved after laser correction. The applied algorithm for the management of patients with combined pathology with pigment dispersion syndrome and myopia is pathogenetically justified, safe, promotes the preservation of visual functions of patients and improves their quality of life.